Relationships between larval fish drift, time of day and discharge in an Ozark stream - Daniel D. Magoulick; Christy L. Graham (Journal of Freshwater Ecology)
We examined the relationship between larval fish numbers and discharge during a high flow event in Bear Creek, Arkansas, a small Ozark stream. Additionally, we examined the relationship between fish numbers and time of day, and the spatial distribution of families and size classes. A total of 3,083 fish from five families were collected. Leuciscidae was the dominant family collected, followed by Percidae, and Catostomidae. Larval fish in Bear Creek were not susceptible to increased discharge from the flood event, as all three families exhibited strong significant negative relationships to discharge at night when discharge began to decline. Larval fish in Bear Creek drifted significantly more at night than during the day, with the exception of large percids, which exhibited no diel pattern. Leuciscidae and small Percidae showed a spatial pattern of distribution across the stream at night, with higher drift densities in near shore nets. The results from our study indicate that fish drift in Bear Creek was an active process, with most larval fish drifting in response to decreased light intensity. We suggest future studies consider the effects of flood intensity on larval fish drift relative to diel periodicity.